O default no crédito bancário para médias e grandes empresas: desvendando as similaridades observáveis no processo decisório de concessão - Silva, Angelo José da (2017)
The present dissertation was aimed at describing how the decision process took place and the kinds of similarities in the default cases of credits granted to medium and large companies served by the corporate segment of a Brazilian bank. The theoretical support took place through three constructs. The first delas with competitiveness through the application of the Corporate Strategy, presented by Porter (1998), for resource management and organizational capabilities, using the VRIO model proposed by Barney and Hesterly (2011). The second construct presents the Decisional Process in the Credit Concession, presented by Silva (2014), which highlights the importance of credit to banks, either by the challenge of intensifying the leverage concession of the result, or by the negative impact of eventual default. The third construct addresses default in banking operations, characterized by Altman, Resti and Sironi (2007), on cases where there is a delay of more than 90 days or when the debtor filed for bankruptcy. The research is theoretically justified by the compilation and facilitation of access to a relevant theoretical framework and the creation of a new construct, broadening the theory about critical factors in the granting of credit. In practical terms, it gives an entrepreneurial diagnosis of how credit is granted, seeking to contribute to the improvement of this process. The (probabilistic) sample of the research was taken over 345 cases, representing a population of 3,361 operations considered in default between January 2016 and April 2017. From this data, 11 (eleven) detectable characteristics were analyzed in the analysis summaries, which supported the decision-making levels. For the quantitative analysis of the data, the descriptive statistics were used, through the measures of position (mean, fashionable median) and dispersion (variance, standard deviation), and the Chi-Square of Pearson. The main contributions of the research were to support financial institutions in the evaluation of the credit granting process, either by the predominance of decision-makers in the cases in default or by the weight given to the common characteristics to the cases, already present at the moment of the analysis of the proposals. The two hypotheses of the research were confirmed, demonstrating first that there were predominant decision-making levels in the cases in default, and secondly that there were detectable characteristics at the moment of credit granting, with relevant frequency in the cases studied. It was highlighted as limitations of the research the period of time of the sample and the fact that only default cases were studied, not investigating honorable operations to verify if the hypotheses would be confirmed.